Designing Skill Cards for New Professions: Easy-to-read Facilitators and Validators - Annamaria KILYENI; Daniel DEJICA; Simona ȘIMON; Marcela FĂRCAȘIU (Scientific Bulletin of the Politehnica University of Timişoara: Transactions on Modern Languages)
Easy-to-read (E2R) can be defined broadly as a text simplification method aimed at making information more accessible to people with reading and learning difficulties, promoted intensely in recent years as a top-priority European strategy for social inclusion. Although validation of E2R content is an important step in the process, neither validation nor those involved in it, i.e. validators and facilitators, get official recognition. The present article focuses on the creation of skill cards for E2R validators and facilitators within the Train2Validate European project, in an attempt to promote the professionalization of validation work.